Transcriptome investigation of anti‐inflammation and immuno‐regulation mechanism of taurochenodeoxycholic acid - Bao, Lige (BMC Pharmacol Toxicol, 2021)
BACKGROUND: Taurochenodeoxycholic acid (TCDCA) is one of the major active components in bile acid. It was proven to have inhibitory activities on inflammation and also participate in host immuno-regulation. TCDCA exerts anti-inflammatory and immuno-regulatory effects through the glucocorticoid receptor (GR) mediated genomic signaling pathway and the G protein-coupled bile acid receptor 5 (TGR5) mediated AC-cAMP-PKA signaling pathway. However, it is unclear whether GR or TGR5 plays an important role in the regulatory effects of TCDCA. In order to further investigate this effects mechanism of TCDCA, the research use the transcriptome to identify the major genes and pathway in the anti-inflammatory and immuno-regulatory effects. METHODS: After the Fibroblast-like synoviocytes (FLS) being treated by different concentrations (10(− 5), 10(− 6) and 10(− 7) M) of TCDCA for 12 h, the resulting mRNA was analyzed by RNA-seq. The differentially expressed genes were screened from sequencing results using bioinformatics techniques. In the next step, other published literature were referred in order to find out whether those genes mentioned above are related to inflammation. The final selected differentially expressed genes associated with inflammation were then validated by q-PCR and western blot assays. RESULTS: Five genes associated with anti-inflammatory and immuno-regulatory effects, include Glyceraldehyde-3-phosphate dehydrogenase (GAPDH), Glutathione peroxidase 3 (GPX3), Serine/arginine-rich splicing factor-9 (SRSF9), Connective tissue growth factor (CTGF) and Cystatin B (CSTB) were identified. TCDCA at the concentrations of 10(− 5), 10(− 6) and 10(− 7) M significantly (p < 0.05) up-regulate the mRNA and protein expression of SRSF9 and GPX3 and also up-regulate the mRNA expression of CSTB, CTGF and GAPDH. RNA-seq results of GPX3 and SRSF9 expression were consistent with q-PCR results, while q-PCR results of CTGF, GAPDH showed inconsistent with their RNA-seq results. Q-PCR result of CSTB expression also showed inconsistent with the RNA-seq result. CONCLUSIONS: The anti-inflammatory and immuno-regulatory activities of TCDCA are proven to be related to the up-regulation expression of GPX3, SRSF9 and CSTB.